Corporate Governance and Tax Avoidance in SRI-KEHATI Firms: The Mediating Role of Financial Performance - Halim, Moh.; Aspirandi, Rendy Mirwan; Suharsono, Riyanto Setiawan; Nastiti, Ari Sita (Universitas Ahmad Dahlan, 2025)
This study aims to examine the role of financial performance in mediating the effect of the proportion of independent commissioners and Big Four auditors on tax avoidance in SRI-KEHATI index companies. Secondary data collected from 25 companies, for the period of 2020 to 2024, were analyzed using SEM PLS to test seven research hypotheses. Results show that the proportion of independent commissioners and the Big Four public accounting firms have a significant positive effect on financial performance and a negative effect on tax avoidance, both directly and indirectly through financial performance. The findings support agency theory, signaling theory, and stakeholder theory, and provide policy implications for regulators and companies in strengthening tax governance and compliance. The novelty of this research lies not only in the use of financial performance as a mediating variable, but more importantly in highlighting the paradox that sustainability-labelled firms (SRI-KEHATI), which are expected to uphold transparency, responsibility, and good governance, may still engage in tax avoidance practices. This study thus provides new insights into the gap between sustainability image and fiscal behaviour, and the role of governance mechanisms in bridging that gap.